To replace or not to replace? — An investigation into the residual strength of damaged rock climbing safety equipment. (February 2016) - May, Michael; Furlan, Stefan; Mohrmann, Holger; Ganzenmüller, Georg C.
Abstract: This paper presents a study on the residual strength of carabiners which have sustained impact damage due to accidental dropping during lead climbing. The question answered here is whether damaged quickdraws can be reused for future climbing or whether they should be replaced. Well defined damages were introduced into the main body and the gate of three different types of quickdraw carabiners. The carabiners were visually inspected and tested for functionality before the residual strength was measured following procedures defined in mountaineering standards. Contrary to common perception no micro-cracks were found within the damaged carabiners. In general, the carabiners tested here showed good resistance to impact damage. Impact on the main body does not seem to affect the residual strength. Impact on the wire gate may result in failure of the gate. However, if the gate is still functional, the strength is not affected by an impact. Highlights: Pre-damage introduced into carabiners using drop tower. Residual strength of carabiners was measured following mountaineering standards. Failure sequence was different for different types of carabiners. Carabiners impacted at the main body did not show a reduction in strength. Carabiners impacted at the gate failed the gate functionality test.